Electromyographic evaluation of the upper lip according to the breathing mode: a longitudinal study - Aldrieli Regina Ambrosio; Paula Cristina Trevilatto; Lídia Parsekian Martins; Ary dos Santos-Pinto; Roberto Hideo Shimizu (Sociedade Brasileira de Pesquisa Odontológica, 2009)
The present study aimed at analyzing and comparing longitudinally the EMG (electromyographic activity) of the superior orbicularis oris muscle according to the breathing mode. The sample, 38 adolescents with Angle Class II Division 1 malocclusion with predominantly nose (PNB) or mouth (PMB) breathing, was evaluated at two different periods, with a two-year interval between them. For that purpose, a 16channel electromyography machine was employed, which was properly calibrated in a PC equipped with an analogue-digital converter, with utilization of surface, passive and bipolar electrodes. The RMS data (root mean square) were collected at rest and in 12 movements and normalized according to time and amplitude, by the peak value of EMG, in order to allow comparisons between subjects and between periods. Comparison of the muscle function of PNB and PMB subjects at period 1 (P1), period 2 (P2) and the variation between periods (Δ) did not reveal statistically significant differences between groups (p < 0.05). However, longitudinal evaluation of the muscle function in PNB and PMB subjects demonstrated different evolutions in the percentage of required EMG for accomplishment of the movements investigated. It was possible to conclude that there are differences in the percentage of electric activity of the upper lip with the growth of the subjects according to the breathing mode.